AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA TUMAPEL KECAMATAN DUDUKSAMPEYAN KABUPATEN GRESIK - Nur Aqidah; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Accountability for village fund management is a form of accountability for the entire set of village fund management activities and policies from the planning stage to the accountability of village fund managers to those who have authority in managing village funds to measure whether the management of village funds is in accordance with applicable regulations. The purpose of village funds is to improve welfare and equitable distribution of rural development through improving public services, advancing the economy, overcoming development gaps between villages and strengthening rural communities as subjects of development. This study uses a descriptive qualitative research method by using the validity of the source triangulation technique. This study aims to analyze the accountability of village fund management in Tumapel Village and identify the factors that influence the accountability of village fund management. The results of this study indicate that the accountability of village fund management in Tumapel Village can be seen from the five dimensions of village fund management accountability, namely accountability for honesty and legal accountability, process accountability, program accountability, policy accountability, and financial accountability. Accountability for managing village funds is appropriate from four dimensions, but program accountability is still not in accordance with applicable regulations and must refer to the village medium term development plan. The realization of village fund management accountability is driven by success factors, namely leader leadership, coordination, openness and clarity, legitimacy and understanding, as well as feedback and evaluation, but there are still obstacles in the accountability of village management, namely lack of wisdom in giving assignments to staff, the unavailability of electronic information media in the form of official websites and social media belonging to the village government in managing village funds.